Cutnell & Johnson physics - Stadler, Shane; Cutnell, John D.; Johnson, Kenneth W. (John Wiley & Sons, 2018)
Cutnell and Johnson has been the Number one text in the algebra-based physics market for over 20 years. Over 250,000 students have used the book as the equipment they need to build their problem-solving confidence, push their limits, and be successful.